2018
DOI: 10.3390/w10080970
|View full text |Cite
|
Sign up to set email alerts
|

Water and Nitrogen Productivity of Potato Growth in Desert Areas under Low-Discharge Drip Irrigation

Abstract: Narrow profit margins, resource conservation issues and environmental concerns are the main driving forces to improve fertilizer uptake, especially for potatoes. Potatoes are a high value crop with a shallow, inefficient root system and high fertilizer rate requirements. Of all essential nutrients, nitrogen (N) is often limiting to potato production. A major concern in potato production is to minimize N leaching from the root zone. Therefore, the main objective of this study was to examine the potato crop char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
2
7
0
1
Order By: Relevance
“…They also found an increase of nitrogen use efficiency (NUE). An increase of both WUE and NUE when optimising drip irrigation was also found by Trifonov et al [75]. However, WUE essentially depends on several factors, including crop management and irrigation scheduling [72].…”
Section: Subirrigationsupporting
confidence: 63%
“…They also found an increase of nitrogen use efficiency (NUE). An increase of both WUE and NUE when optimising drip irrigation was also found by Trifonov et al [75]. However, WUE essentially depends on several factors, including crop management and irrigation scheduling [72].…”
Section: Subirrigationsupporting
confidence: 63%
“…Factors that affect nitrate nitrogen leaching include irrigation schedule, climate change and nitrogen fertilization mode. As climatic factors are uncontrollable, nitrogen leaching can be reduced via adequate management of irrigation and fertilization (Sui et al, 2015; Trifonoy et al, 2018). He et al (2012) proposed that frequent irrigation will cause nitrogen leaching, because frequent irrigation will increase the soil moisture content and rainfall will not be stored in the soil and will percolate into deep soil layers, thus promoting nitrogen leaching; in contrast, frequent application of a small amount of N fertilizer is beneficial for crop absorption of nutrients and nitrogen leaching may be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The highest yield was measured in sprinkler-irrigated plots at the 60 g m −3 nitrogen concentration levels. Trifonov et al [21] studied potato crop characteristics under low discharge from a drip irrigation system, to determine the optimal dosses of irrigation and fertigation. Their results suggested that drip and fertigation systems were water-productive systems when available agricultural soils were not a limiting factor.…”
Section: Introductionmentioning
confidence: 99%